Donald Duk : a novel - Chin, Frank, 1940- (Coffee House Press ; Distributor, Consortium Book Sales and Distribution, 1991)
On the eve of the Chinese New Year in San Francisco's Chinatown, twelve-year-old Donald Duk attempts to deal with his comical name and his feelings for his cultural heritage.